Sustainable energy planning in Slovenian municipalities - Kovačič Lukman, Rebeka (JET on-line, 2016)
One of the European initiatives responding to the global challenges of climate change, on the local level, is the Covenant of Mayors (CoM), a voluntary agreement of cities and municipalities to improve energy efficiency, the usage of renewable resources, and carbon dioxide (CO2) reduction by 2020. Our study represents a process of sustainable energy planning and analyses two Sustainable energy action plans (SEAPs) in Slovenia, offering an in-depth view of the improvements, which are composed of technological measures and "soft" measures, such as education and awareness raising. Further recommendations are made regarding the SEAP preparation, implementation, and monitoring, considering a systematic and holistic approach towards more sustainable local communities.
Keywords: energetska učinkovitost; energy efficiency; energy management; Slovenia; Slovenija; sustainable energy action plan; trajnostno energetsko načrtovanje